A inclusão digital como direito fundamental: fomento a promoção do sujeito real no campo virtual face aos riscos inerentes à vulnerabilidade digital - Estevam, Marcelo Henrique de Sousa (2024)
The present research proposes a deep reflection on the promotion of the real subject in the virtual context, considering the complex capitalist situation and the apparent (non) neutrality of the network. In view of this, it investigates the identity of the real subject in the virtual field and defends the need to promote it, going beyond the mere mechanical ability to access digital public space. To this end, it addresses issues of digital inclusion (and not exclusion), highlighting digital inclusion as a fundamental issue of citizenship, as well as exploring the emancipation of the real subject in the virtual field as a means of balance between the existential and virtual legal plane. Furthermore, it focuses on the duty to build an "ethical pavilion" on the internet through the legal principle of human dignity. Thus, it explores Jürgen Habermas' theory of society, highlighting the role of democratic and inclusive dialogue in the virtual field and examines Law as a guarantee of consensus among subjects on the internet, in addition to discussing the emancipatory possibilities of Law to create an ethical environment in the virtual field, also based on the legal principle of human dignity. Furthermore, it argues that digital inclusion is a fundamental right, analyzing Brazilian laws related to cybersecurity and the protection of vulnerable people on the internet. It also highlights the contrast between the indispensability of internet access and the factors that perpetuate digital exclusion, as well as addressing the legal interpretation of digital inclusion as a constitutional value for the better protection and promotion of the vulnerable in the face of the intrinsic risks of digital vulnerability. Furthermore, it examines the contribution of digital inclusion to the effectiveness of promoting the real subject on the internet, addressing topics ranging from the protection of privacy to the responsibilities of the State and civil society in promoting the vulnerable in the virtual field. Finally, a critical analysis is made of the fragility of the real subject in the face of digital risks, aggravated by the covid-19 pandemic, highlighting the need for prevention and addressing issues relevant to the contemporary context in order to guarantee the legitimate promotion of the vulnerable in the virtual field.